2012
DOI: 10.2478/v10057-012-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age on Stroop Interference in Clinical vs. Healthy Groups of Children

Abstract: The Effects of Age on Stroop Interference in Clinical vs. Healthy Groups of Children The Stroop task is widely used to assess attentional dysfunction due to a frontal or frontoparietal deficit and is also thought to be related to the maturation of the prefrontal cortex. The study aimed to prove the diagnostic usefulness of the Polish Names and Colors Interference Test (TINiK) in a clinical setting and to investigate the pattern of performance on four TINiK subtasks according to the type of brain damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The classic pattern of performance for Stroop tasks with children (Bub, Masson, & Lalonde, 2006;Comalli et al, 1962;Okuniewska et al, 2012) and adults (MacLeod & MacDonald, 2000;Strauss et al, 2006) was found in the present study. The naming times and number of errors on the ST increased from the Color phase to the Word phase and finally to the Interference phase.…”
Section: Stroop Tasksupporting
confidence: 71%
See 1 more Smart Citation
“…The classic pattern of performance for Stroop tasks with children (Bub, Masson, & Lalonde, 2006;Comalli et al, 1962;Okuniewska et al, 2012) and adults (MacLeod & MacDonald, 2000;Strauss et al, 2006) was found in the present study. The naming times and number of errors on the ST increased from the Color phase to the Word phase and finally to the Interference phase.…”
Section: Stroop Tasksupporting
confidence: 71%
“…The Stroop paradigm evaluates selective attention and cognitive flexibility by measuring shifting ability with regard to suppressing a usual response in favor of an unusual response (Strauss et al, 2006). Performance on the ST is sensitive to dysfunction of the frontal lobes, including neuropsychiatric disturbances (e.g., attention-deficit/hyperactivity disorder, anxiety, autism, and depression; Assef, Capovilla, & Capovilla, 2007; Ergür et al, 2012; Homack & Riccio, 2004; Lansbergen, Kenemans, & van Engeland, 2007; Okuniewska, Maryniak, & Healthy Groups of Children, 2012).…”
Section: Stroop Testmentioning
confidence: 99%
“…Cognitive control was assessed using three widely used cognitive control tasks suitable for use with children as young as 8 years-old: the Stroop Color-Word Test (SCWT; e.g., Homack & Riccio, 2004;Okuniewska & Maryniak, 2012), the N-Back test (e.g., Pelegrina et al, 2015) and the Wisconsin Card Sorting Test (WCST; Chelune & Baer, 1986) . For the SCWT and N-Back, practice trials were provided to ensure that each child understood the instructions.…”
Section: Cognitive Control Tasksmentioning
confidence: 99%